Preoperative Radiographic Parameters to Predict a Higher Pseudarthrosis Rate After Anterior Cervical Discectomy and Fusion. Issue 23 (1st December 2017) - Choi, Sung H.; Cho, Jae H.; Hwang, Chang J.; Lee, Choon S.; Gwak, Hyun W.; Lee, Dong-Ho
Abstract : Study Design: Retrospective study. Objective: To determine whether postoperative pseudarthrosis can be predicted from specific preoperative radiograph measurements. Summary of Background Data: Various factors reportedly influence the occurrence of pseudarthrosis after anterior cervical discectomy and fusion (ACDF). However, to our knowledge, there are no reports on the relationships between preoperative radiographic parameters and pseudarthrosis. Methods: We analyzed 84 consecutive patients (45 males, 39 females, mean age, 58.9 ± 11.2 yrs) who underwent ACDF. In all patients, allografts filled with local chip bone were inserted after discectomy and anterior plating was performed. On preoperative plain radiographs, we analyzed C2–C7 sagittal vertical axis, T1 sagittal slope, segmental motion, global cervical motion, and location of fusion segments. Pseudarthrosis was diagnosed as interspinous motion >1 mm with superjacent interspinous motion ≥4 mm on magnified dynamic lateral radiographs. Multivariate logistic regression was used to analyze the risk factors for pseudarthrosis and the receiver operating characteristic (ROC) curve was used to define a cutoff value. Results: One hundred and twenty-five segments from 84 patients were included. The pseudarthrosis rate was 29% based on number of patients (24/84) and 20% based on number of segments (25/125). Multilevel surgery and segments at the lowest levels showed higher pseudarthrosis rates ( P = 0.01). Per multivariate logistic regression analysis, greater preoperative segmental motion, greater preoperative T1 sagittal slope, and C6–7 segments were associated with a higher risk of pseudarthrosis (all P < 0.05). A segmental motion cutoff value of 12° demonstrated pseudarthrosis with sensitivity of 87%, specificity of 84%, and area under the curve of 0.899, indicating moderate accuracy. Conclusion: Greater preoperative segmental motion, greater preoperative T1 sagittal slope, and lower fusion levels could be risk factors for pseudarthrosis following ACDF. Preoperative segmental motion >12° is likely to be an important indicator of the development of pseudarthrosis. Level of Evidence: 3